Antibacterial and antibiofilm activities of Malaysian trigona honey against pseudomonas aeruginosa and streptococcus pyogenes - Alkafaween, Mohammmad Abdulraheem M.
Pseudomonas aeruginosa is an opportunistic pathogen that has been implicated in a wide range of infections, such as endocarditis, folliculitis, keratitis, meningitis, pneumonia, urinary tract infections, and wound infections. Streptococcus pyogenes is an important human opportunistic pathogen that is responsible for a number of diseases, ranging from skin and soft tissue infections. Biofilm contributes to approximately 80% of the total microbial infections including P. aeruginosa and S. pyogenes. Honey is a natural product that has been widely used for its therapeutic effects. Malaysian Trigona honey (MTH) is effective against pathogenic bacteria in inhibiting planktonic antibiotic sensitive strains and antimicrobial resistant organisms. However, there are limited in vitro studies on antibacterial and antibiofilm activities of MTH against P. aeruginosa and S. pyogenes. Therefore, the purpose of this study was to investigate the antibacterial, antibiofilm and antivirulence activities of MTH against both bacteria. The antibacterial, antibiofilm and antivirulence activities of MTH against both bacteria were investigated by agar well diffusion, Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC), disruption of microcolony, growth curve, time-kill curve, scanning electron microscopy (SEM), microtiter plate and reverse transcription-quantitative real time polymerase chain reaction (RT-qPCR). Agar inhibition assay showed that MTH at 20% has antibacterial activity against P. aeruginosa and S. pyogenes with an inhibition zone of 7.2±0.2 mm and 8.0±OA mm respectively. The results showed that MTH possessed the lowest MIC and MBC values against both bacteria with 20% and 25% respectively. In addition, the MICso and MlC90 for MTH against both bacteria were 19% and 24% respectively. MTH was found to disrupt microcolony formation in both bacteria at 20% MTH. Growth curves demonstrated that no growth of both bacteria at 20% (MIC) MTH. In time-kill curve, treatment of both bacteria with 25% MTH for 24 hours resulted in decreases of 4-log reduction (P < 0.05) in total viable counts. Additionally, both bacteria could not be recovered after 9 hours incubation with 2xMIC of MTH. The results indicate the suitability of MHB and TSB medium for the formation of P. aeruginosa and S. pyogenes biofilms. The lowest concentration of 20% MTH was found to degrade and inhibit biofilm formation. Changes in the total viable cell count of P. aeruginosa and S. pyogenes biofilm showed a 2.1x106 and 2.0xl06 reduction respectively after exposure to MTH. Using SEM, loss of structural integrity and marked changes in cell shape were observed for both bacteria following treatment with MTH. The genes expression of algD, oprF, oprB, oprH, jleN, jleQ, jleR, jliC and jliA in P. aeruginosa were downregulated ranging from 2.0 fold to 11.11 fold. Meanwhile, sof sjbl, emml3, scpA andfisY in S. pyogenes were downregulated ranging from 2.87 fold to 9.23 fold. This study demonstrated that MTH has antibacterial and antibiofilm activities and has potential as a therapeutic agent for microbial infection particularly against P. aeruginosa and S. pyogenes. This study revealed that MTH inhibits both planktonic and biofilm P. aeruginosa and S. pyogenes through the downregulation of genes required for cell envelope stability and motility.